2021
DOI: 10.1016/j.adolescence.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Improving cognitive functions in adolescents with learning difficulties: A feasibility study on the potential use of telerehabilitation during Covid‐19 pandemic in Italy

Abstract: Introduction. Learning disabilities are due to genetic and/or neurobiological factors that alter brain functioning by affecting one or more cognitive processes related to learning. This study aimed to assess the efficacy of cognitive telerehabilitation in adolescents with learning disabilities to overcome the treatment problems related to the COVID‐19 pandemic lockdown. Methods. Twenty‐four patients diagnosed with Unspecified Learning Disability (mean ± SD age: 18.2 ± 2.9 years; 50% male) were enrolled in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…These profiles suggest the effect of MemoRAN on the consolidation of lexical and orthographic representations without the generalisation to semantic-contextual inference strategies. The results that emerged are in line with what is found in the literature about the efficacy of tele-rehabilitation in SLD [ 36 , 37 , 38 , 39 , 47 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These profiles suggest the effect of MemoRAN on the consolidation of lexical and orthographic representations without the generalisation to semantic-contextual inference strategies. The results that emerged are in line with what is found in the literature about the efficacy of tele-rehabilitation in SLD [ 36 , 37 , 38 , 39 , 47 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, recent research on transparent spelling, such as that of the Italian language, has demonstrated the effectiveness of software tailored to help children and young people with SLD at home [ 31 , 36 , 37 ]. The very recent study by Maggio and colleagues (2021, [ 38 ]) shows how, even in a sample of adolescents, the use of tele-rehabilitation that combines the training of specific instrumental deficits and executive functions can provide valid support for the improvement of weak cognitive abilities in SLD. In this study, the adolescents used a 60 min telerehabilitation program for five days a week for four weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of the Internet, more knowledge is mainly obtained through network resources, and the effect of dyslexia on "information seeking" behavior has gradually attracted the attention of dyslexia researchers (132,133). In addition, the emergence of a new keyword COVID-19 in the past 2 years also showed that during the COVID-19 epidemic, researchers began to study the impact of the epidemic on dyslexia research (115,(134)(135)(136)(137). As the international exchange of dyslexia research continues to grow, scientists are aware that differences in education-related legislation in different countries may lead to persistent differences countries and had the biggest collaboration network in the dyslexia research.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to support students with dyslexia during the pandemic period (e.g., Arifa, 2021 ; Maggio et al, 2021 ; Shaw et al, 2022 ). These studies unanimously agree on the negative impact of the COVID-19 pandemic on the health and well-being of children with disabilities and their families, especially those with developmental dyslexia, and they recommend providing and supporting conscious post-disaster trauma treatment practices.…”
Section: Literature Reviewmentioning
confidence: 99%